Forecasting Inflation in a Non-Eurozone EU Country: An Econometric Analysis of Poland - Gao , Runjia (Transactions on Economics, Business and Management Research, 2024)
Poland, an emerging economy in eastern Europe, became a member of the EU since 2004, however, due to economic and political reasons, the country is not yet in the Eurozone and still maintained its own central bank, independent monetary policies, as well as their local currency Zloty. Historically, the country has experienced high inflation during its systematic economic reformation after the end of its communist era, but it successfully maintained a low inflation rate afterwards until the start of the Ukrainian War in 2022. Through utilizing Python, this research analyzed the effect of both Poland’s and Eurozone’s monetary policy as well as key economic and geopolitical events on Poland’s inflation rate. The research discovered that the only exogeneous factors that influenced Poland’s inflation rate is its domestic monetary policy and the Ukrainian War. The research also made a 12-month ahead forecast on Poland’s inflation rate and made recommendations to global corporations amid the uncertainties.